On What a Garden Can Remember. The Jardin du Québec and the Floralies internationales 1980 (Montreal) - Despard, Erin (Intermédialités / Intermediality, 2020)
Drawing from work in progress at a series of somewhat neglected public gardens in Montreal, this article explores what a transhistorical, materialist approach to the intermedial study of public gardens might look like. It focuses on the relationship between a documentary film about the gardens made in 1980 (Bonjours Floralies, Bernard Beaupré), and one of the gardens in the present, as a means to develop a novel point of view on the historical and phenomenological functioning of both.